Monday

July 28, 2014

July 28, 2014

Posted by **Anonymous** on Monday, June 6, 2011 at 12:13pm.

- math -
**Mgraph**, Monday, June 6, 2011 at 1:02pmx^2+2xy+y^2+x+y-2=(x+y+2)(x+y-1)

y=-x-2

y=-x+1

**Related Questions**

math - show that the equation x^2+2xy+y^2+x+y-2=0 rebresent two paralil lines ...

Geometry - If two non parallel lines are perpendicular to two other straight ...

Calculus - dy/dx= (y^2 -1)/x 1. Give the general equation of the curves that ...

Math - Solve 2x-y+3z=8 x-6y-z=0 -6x+3y-9z=24 Did you notice that your third ...

Math 2 - You should make two selections from the list below. Which two of the ...

Vector - The two lines with the equation r=(1,2,-44)+ t(k+1, 3k+1,k-3) and x=2-...

Calculus - The line that is normal to the curve x^2=2xy-3y^2=0 at(1,1) ...

Math - Show the two lines (x/2-1/2)=(y/3-2/3)=(z/4-3/4) and (x/5-4/5)=z ...

HELP WITH ALGEBRA!! - 6. What happens to the graph of the line y = 3x -2 when ...

Algebra - The teacher wants us to do the following problem by using substitution...